Rebound COVID-19 after Paxlovid in 2 related family members - Periyasamy, Petrick; Tan, Li Fen; Kori, Najma; Zainulabid, Ummu Afeera (2022)
On May 24, 2022, the CDC issued a healthcare advisory after reports of COVID-19 symptoms returning (COVID-19 rebound) in certain patients two to eight days after treatment with Paxlovid (Ritonavir-Boosted Nirmatrevir). We described two patients who experienced a rebound of COVID-19 after receiving Paxlovid treatment.